The Effect of Fermentation with Kefir Grains on the Physicochemical and Antioxidant Properties of Beverages from Blue Lupin (Lupinus angustifolius L.) Seeds - Łopusiewicz, Łukasz (Molecules, 2020)
Plant derived fermented beverages have recently gained consumers’ interest, particularly due to their intrinsic functional properties and presence of beneficial microorganisms. Three variants containing 5%, 10%, and 15% (w/w) of sweet blue lupin (Lupinus angustifolius L. cv. “Boregine”) seeds were inoculated with kefir grains and incubated at 25 °C for 24 h. After processing, beverages were stored in refrigerated conditions (6 °C) for 21 days. Changes in microbial population, pH, bioactive compounds (polyphenolics, flavonoids, ascorbic acid), reducing sugars, and free amino acids were estimated. Additionally, viscosity, firmness, color, and free radicals scavenging properties were determined. Results showed that lactic acid bacteria as well as yeast were capable of growing well in the lupin matrix without any supplementation. During the process of refrigeration, the viability of the microorganisms was over the recommended minimum level for kefir products. Hydrolysis of polysaccharides as well as increase of free amino acids was observed. As a result of fermentation, the beverages showed excellent DPPH, ABTS(+·), (·)OH, and O(2)(−) radicals scavenging activities with a potential when considering diseases associated with oxidative stress. This beverages could be used as a new, non-dairy vehicle for beneficial microflora consumption, especially by vegans and lactose-intolerant consumers.